2000
DOI: 10.1038/71600
|View full text |Cite
|
Sign up to set email alerts
|

Reduced stability of retinoblastoma protein by gankyrin, an oncogenic ankyrin-repeat protein overexpressed in hepatomas

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers in Asia and Africa, where hepatitis virus infection and exposure to specific liver carcinogens are prevalent. Although inactivation of some tumor suppressor genes such as p53 and p16INK4Ahas been identified, no known oncogene is commonly activated in hepatocellular carcinomas. Here we have isolated genes overexpressed in hepatocellular carcinomas by cDNA subtractive hybridization, and identified an oncoprotein consisting of six ankyrin repeats (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
346
2
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(365 citation statements)
references
References 18 publications
11
346
2
6
Order By: Relevance
“…This study also showed that TBP-1 has tumour-suppressive properties, a finding confirmed subsequently by other groups (Pollice et al, 2007). Several proteins, whose cellular levels are regulated by TBP-1, may be involved in mediating its tumour-suppressive effects, including p14ARF (Pollice et al, 2007), HIF1a (Corn et al, 2003) and Rb (Higashitsuji et al, 2000). Our findings suggest that negative regulation of Fra-1 levels may also contribute to the ability of TBP-1 to act as a tumour suppressor.…”
Section: Discussionsupporting
confidence: 87%
“…This study also showed that TBP-1 has tumour-suppressive properties, a finding confirmed subsequently by other groups (Pollice et al, 2007). Several proteins, whose cellular levels are regulated by TBP-1, may be involved in mediating its tumour-suppressive effects, including p14ARF (Pollice et al, 2007), HIF1a (Corn et al, 2003) and Rb (Higashitsuji et al, 2000). Our findings suggest that negative regulation of Fra-1 levels may also contribute to the ability of TBP-1 to act as a tumour suppressor.…”
Section: Discussionsupporting
confidence: 87%
“…Somatic inactivating mutations and homozygous deletions of the gene are rarely observed in HCC (Biden et al, 1997;Jin et al, 2000). Finally, Gankyrin was found to be overexpressed in all cases of 34 analysed HCC (Higashitsuji et al, 2000). Moreover, the authors found that Gankyrin induced anchorage-independent growth and tumorigenicity in NIH/3T3 cells.…”
Section: )mentioning
confidence: 92%
“…36 In addition, PSMD10/ Gankyrin, a subunit of the 26S proteasome that accelerates the degradation of retinoblastoma, is overexpressed in HCC. 37 Also, enhanced activation of ubiquitin-dependent protein degradation may account for deregulation of cell cycle control and faster cell prolifera- tion in the poor survival group (subclass A). Therefore, deregulated components in ubiquitin-mediated protein degradation may provide attractive therapeutic targets for novel HCC treatment modalities.…”
Section: Discussionmentioning
confidence: 99%